Postoperative Complications After Gynecological Surgry in Al Kut City - khudaer, Tabark Salman; AL-Sarray, Atta Ah Mousa; Rasheed, Qahtan Adnan (South Eastern European Journal of Public Health, 2024)
Introduction: Post-operative problems are common. How the complications develop depends on the kind of operation, the preoperative treatment, and the patient's pre-existing comorbid condition. Problems following surgery can be divide into two categories: general and procedure-specific, as well as having emerged promptly, early, or late. Objectives: To determine the postoperative complications type after gynecological surgery in AL-Kut city. Methodology: A cross-sectional study had carried out in AL-Kut City, at the AL-Zahraa Teching Hospital and AL-Kut Hospital for Gynecology and Pediatrics. The seven-month data collection period started on October 16, 2023, and ended on May 16, 2024. Results: 400 female participants, ranging in age from 13 to 72, were be studied. The age distribution of the patients was 31.5 ±10, with the age group 24-34 accounting for the largest percentage of patients (41%) and the age group over 45 accounting for the lowest percentage (7.8%). In terms of marital status, the largest proportion of women (96.2%) were married, while the lowest (1.3%) were widowed. 51.2% of patients lived in urban areas, compared to 48.8% in rural ones. Patients with two to three children had the highest number of parities (34.8%), whereas 18% of patients did not have any parties. 31.8% of patients had an abortion, whereas 68.3% did not. Of which 44.3% had considered as normal BMI, 34.5% of people are overweight, 12% belong to the obese I, 4.3% to the obese II, and 4.5% are morbidly obese. Based on the patients' past medical history, hypertension was the most common ailment detected, accounting for 30.3% of cases (chronic HTN 13%, gestational HTN 17.3%), while diabetes patients made up 9.5% (chronic D.M. 6.5%, gestational D.M. 3%). Classification of Complications: 90.3% of complications occurred within 48 hours, whereas 51.3% developed intraoperative complications. Finally, 50.2% of patients experienced a late problem 48 hours later. Conclusion: The study discovered a link between complications after gynecologic surgery and pre-operative blood transfusion and hospital stay. Hemorrhage, anesthesia difficulties, and cardiac arrhythmia were significant, were the most common late complications among the patients. On the other hand, late complications had linked to surgical duration, number of parities, and age.